Healthy Lifestyle as A Socio-Cultural Phenomenon - Ochilova Faridakhon Kudrat Qizi (Indonesian Journal Publisher, 2025)
The article examines the philosophical evolution of the concept of a healthy lifestyle (HLS) from Antiquity to the present day, emphasizing its importance as a socio-cultural and ethical phenomenon. It demonstrates that HLS is not only a condition for individual well-being but also a strategic resource for societal development, requiring interdisciplinary and philosophical reflection. Also explores the role of philosophy in shaping the concept of a healthy lifestyle and its influence on modern educational systems and public initiatives aimed at promoting healthy living